Blends of polybenzoxazine/poly(acrylic acid): hydrogen bonds and enhanced performances. Issue 8 (10th April 2017) - Wang, Bin; Yang, Po; Li, Yiqiao; He, Yueshan; Zhu, Rongqi; Gu, Yi
Abstract: This work focuses on exploring the role of the additional hydrogen bond donor moiety‐containing polymer poly(acrylic acid) (PAA) in the hydrogen bonds and properties of polybenzoxazines. Thorough studies showed that PAA could not only decrease the curing temperature of benzoxazine resin, but also give additional hydrogen bond donors that were beneficial to the hydrogen bonding interactions and performances of polybenzoxazine/PAA blends. As the hydrogen bonds varied, the glass transition temperature and tensile modulus of the polymer blends changed in accordance with the hydrogen bonds. The results revealed that the introduction of the hydrogen bond donor moiety‐containing polymer was beneficial for hydrogen bonding interactions, which could improve the performances of polybenzoxazines. This novel insight is anticipated to be of help to researchers in the development of more polybenzoxazines and polybenzoxazine blends with enhanced properties. © 2017 Society of Chemical Industry Blends of polybenzoxazine/poly(acrylic acid): hydrogen bonds and enhanced performances: Poly(acrylic acid) can not only decrease the curing temperature of benzoxazines, but also give additional hydrogen bond donors that are beneficial for the hydrogen bonding interactions and performances of polybenzoxazines.